Diindenopyrazines: electron-deficient arenes - Brosius, Victor; Weigold, Svenja; Hippchen, Nikolai; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F. (Chemistry - a European journal, 2021)
The syntheses, properties and application of the air-stable electron acceptors, diindenopyrazines 4 a-g are reported demonstrating the introduction of functional aryl groups in the 6- and 12-positions. The targets are accessible on the hundred milligram to gram scale. The structure of the aryl groups in 4 a-g modulates their solubility, redox potentials and optical properties. The introduction of electron-poor aryl groups to the electron-poor diindenopyrazine backbone reduces the electron affinity to −4 eV, making the compounds attractive as n-semiconductors. A simple organic field-effect transistor of 4 e -without optimization- shows electron transport with a mobility of up to 0.037 cm2 V−1 s−1.
Gesehen am 12.04.2023